PENGARUH GOOD GOVERNANCE, KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN TERHADAP KINERJA ORGANISASI (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Kepulauan Meranti) - Vini Destriyani; Taufeni Taufik; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of Good Governance, the Quality of Human Resources, and Information Technology Utilization Internal Control Performance Against Local Government Organisation. The population in this study was 28 SKPD in Kepulauan Meranti. Sampling technique is purposive sampling technique. Data analysis techniques to test hypotheses using multiple analysis approach. These results indicate that good governance affects the tcount> ttable 2.063> 2.009, Quality of Human Resources have significant influence with t value> ttabel 7.447> 2.009, a significant effect on Information Technology Utilization to the value t count> t table 2.076> 2.009 and Control Internal significant effect with the value t count> t table 2.491> 2.009 on the performance of the organization. While the R-square value that is equal to 0.748, which means 74.8% of the independent variable in this study could affect the dependent variable. While the remaining 25.2% is influenced by other variables not examined in this study as leadership styles, organizational culture budget participation, the application of accounting information, communication, means of support, organizational commitment, organizational communication, leadership, implementation of decentralized organizational structure characteristics of the budget, the budget clarity, feedback budget, and budget evaluation.Keywords: Good Governance, Human Resources Quality, Information Technology, Internal Control, and Performance.